6(2-v)-v=2(v+1)

Simple and best practice solution for 6(2-v)-v=2(v+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2-v)-v=2(v+1) equation:



6(2-v)-v=2(v+1)
We move all terms to the left:
6(2-v)-v-(2(v+1))=0
We add all the numbers together, and all the variables
6(-1v+2)-v-(2(v+1))=0
We add all the numbers together, and all the variables
-1v+6(-1v+2)-(2(v+1))=0
We multiply parentheses
-1v-6v-(2(v+1))+12=0
We calculate terms in parentheses: -(2(v+1)), so:
2(v+1)
We multiply parentheses
2v+2
Back to the equation:
-(2v+2)
We add all the numbers together, and all the variables
-7v-(2v+2)+12=0
We get rid of parentheses
-7v-2v-2+12=0
We add all the numbers together, and all the variables
-9v+10=0
We move all terms containing v to the left, all other terms to the right
-9v=-10
v=-10/-9
v=1+1/9

See similar equations:

| 2)22=1+8a+5 | | 2(3n+1.5)=5(n–4)​ | | 15-9(2x+3)=-16x+40 | | 3(x-2)=2x-4+x-1 | | 10y+19.95=139.96 | | 2^x+2+2^x+1=9 | | X/3+6=x/9-10 | | 12x+10=5-6x | | -25-10r=5(-6+2r) | | 4x2-12=4x2+2x-7 | | 84=-12+b | | 12x+14-3x+7=7(x+3)+2x | | 6x²+15x+135=0 | | -7+4(c+8)=-2(c-1) | | 3(x-1)+4x=4 | | x-2(1/4)(x-1/2)=1/6(2x+1)+1/3 | | 7y+-4y=-18 | | 8+.4x=4+.6x​ | | 11–5a=51 | | 6x-20=-14x+4 | | 3^2+10x–117=0 | | 5x-7=4x-1= | | 1-5x/8=3 | | 350+50x=800 | | 27-15=2(x-3)= | | 1.4t(t-3.1)=5.8 | | 5x2x2=10x5 | | 24=8x-4(x-8) | | 7g=9g−2g | | 12=10+x/5 | | 1.06g+-3=0.71 | | 5x+23+4x+31=180 |

Equations solver categories